2021
DOI: 10.3390/horticulturae7120591
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Quality and Yield of Three Highbush Blueberry (Vaccinium corymbosum L.) Cultivars Grown in Two Planting Systems under Different Protected Environments

Abstract: Due to the increasing interest in highbush blueberry (Vaccinium corymbosum L.) among consumers, together with the problems of climate change and specific substrate requirements, a novel approach to intensive blueberry production is required. Here, ‘Duke’, ‘Aurora’, and ‘Brigitta’ blueberry cultivars were planted under the protective environments of a high tunnel and black hail net, each using ridge and pot planting systems. The high tunnel increased the maximal air temperature on average by 7.2 °C compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Although 'Brigitta' showed a significantly higher h • value and lower fruit firmness, these differences were negligible and could not be detected by the naked eye. These results are also in agreement with our previous study [23].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although 'Brigitta' showed a significantly higher h • value and lower fruit firmness, these differences were negligible and could not be detected by the naked eye. These results are also in agreement with our previous study [23].…”
Section: Discussionsupporting
confidence: 94%
“…The similar growth rates between cultivars within the individual planting methods suggest that growth is primarily a cultivar, and secondarily an environmental, trait. 'Duke' originates from Maryland, USA, 'Aurora' from Michigan, USA, and 'Brigitta' from Victoria, Australia [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Highbush blueberry berries, according to researchers from Ukraine (Shevchuk et al,2021), France (Brat et al, 2006) and other countries of the world (Smrke et al, 2021), are a source of nutritional biologically active substances that are useful for the human body. They contain a significant number of compounds that have an antioxidant effect, in particular: vitamin C, polyphenols, flavonoids, anthocyanins, and chalcones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to other crops, blueberries are a significant source of anthocyanins (Grace et. al., 2019;Smrke et. al., 2021).…”
Section: Anthocyanin and Chalcone Content In Fresh And Defrosted High...mentioning
confidence: 99%
“…According to recent studies, anthocyanins are the most represented group of phenolics found in blueberry fruit [13]. Their accumulation in blueberry peel contributes to both peel color (red, blue, purple) and fruit nutritional value [3,4,14], suggesting a positive correlation between ripening stage, anthocyanin content, peel color intensity, and fruit quality [5,15]. In general, genetic background (i.e., cultivar) defines which anthocyanins occur in blueberry fruit, while environmental factors determine their content [16].…”
Section: Introductionmentioning
confidence: 99%